Characteristics of physical environment in Arabic classroom: A preliminary study in Malaysian public universities - Mohd Ala-Uddin, Othman; Che Mohd Zaid, Yusof; Nurul Ain, Chua; Kasyfullah, Abdul Kadir; Rusdi, Ab Majid; Jumadil, Saputra (2021)
This study discusses the characteristics of the physical environment in the classroom at Malaysian public universities. The study of the physical environment is essential because the mastery of Arabic learners is crucial. Research is usually done only on aspects of teaching and learning. While aspects of the environment are rarely found, therefore, this study will describe the characteristics of the physical environment conducive to teaching and learning in the classroom at Malaysian public universities. A total of 494 students from eight Malaysian public universities responded to the questionnaire distributed. This study uses descriptive quantitative research methods. The instruments are composed of four structures, namely furniture and equipment, lighting, technology and air quality indoors. The researcher uses the Statistical Package for Social Science (SPSS-22) software for factor analysis ( EFA), and factor validation analysis (CFA). The result found that the nature of the physical learning environment in the Arabic classroom has been interpreted from the analysis of the perceptual score obtained. Although students at public universities in Malaysia regard the Arabic language learning atmosphere in this classroom favourably, they wish to enhance the real learning experience in the classroom in all four constructs.